2020
DOI: 10.3393/ac.2019.10.16.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Postoperative Outcomes of Patients Presenting With Upper Gastrointestinal Tract Crohn Disease

Abstract: Purpose: Upper gastrointestinal (GI) tract involvement in Crohn disease (CD) is rare and effectiveness of surgical treatment is limited. The aim of this study was to evaluate characteristics and surgical outcomes of upper GI CD.Methods: Medical records of 811 patients who underwent intestinal surgery for CD between January 2006 and December 2015 at a single institution were reviewed. Upper GI CD was defined by involvement of the stomach to the fourth portion of duodenum, with or without concomitant small/large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
12
1
1
Order By: Relevance
“…Most patients achieved good outcomes after bypass surgery and/or primary repair. In contrast to previous studies that reported that the most common surgical indication for patients with CD was obstruction [10], 58.3% of the patients in the study by Moon et al [9] underwent surgery for penetrating fistula. Half of the patients with a fistula might have had penetration of distal CD such as the ileum or transverse colon.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…Most patients achieved good outcomes after bypass surgery and/or primary repair. In contrast to previous studies that reported that the most common surgical indication for patients with CD was obstruction [10], 58.3% of the patients in the study by Moon et al [9] underwent surgery for penetrating fistula. Half of the patients with a fistula might have had penetration of distal CD such as the ileum or transverse colon.…”
contrasting
confidence: 62%
“…However, information regarding surgery for UGI CD is sparse and has not been reported for patients with CD in Korea. Moon et al [9] analyzed the outcomes of adult patients who underwent surgery for UGI CD during a 20-year period at a single institution. The perioperative outcomes of 24 patients (2.96% of the total cohort) who underwent surgery for UGI CD were compared with those of 787 patients (97.04% of the total cohort) with only distal CD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals were clinically assigned according to the Montreal classification system, initially at baseline, for CD patients. Physician assessed Montreal classifiers were denoted by disease status such as B1 (inflammatory), B2 (stricturing), or B3 (penetrating); and inflammation location such as L1 (ileal), L2 (colonic), and L3 (ileal-colonic) [13]. Disease severity classifications, demographics, and clinical information were collected for each patient at time of enrollment and during follow-up, are provided in Table 1 along with other patient metrics included age, sex, disease type, disease behavior, inflammatory status and inflammation on disease location.…”
Section: Cohortmentioning
confidence: 99%
“…Individuals were clinically assigned according to the Montreal classi cation system, initially at baseline, for CD patients. Physician assessed Montreal classi ers were denoted by disease status such as B1 (in ammatory), B2 (stricturing), or B3 (penetrating); and in ammation location such as L1 (ileal), L2 (colonic), and L3 (ileal-colonic) 13 . Disease severity classi cations, demographics, and clinical information were collected for each patient at time of enrollment and during follow-up, are provided in Table 1 along with other patient metrics included age, gender, disease type, disease behavior, in ammatory status and in ammation on disease location.…”
Section: Cohortmentioning
confidence: 99%